Differential modulation of voltage-gated sodium channels by nerve growth factor in three major subsets of TrkA-expressing nociceptors - Meyer, Irina; Prato, Vincenzo; Arcourt, Alice; Taberner, Francisco J.; Lechner, Stefan (Molecular pain, 2018)
Nerve growth factor is an inflammatory mediator that induces long-lasting hyperalgesia, which can partially be attributed to nerve growth factor-induced sensitization of primary afferent nociceptors. It was shown that nerve growth factor increases the excitability of polymodal C-fibre nociceptors by modulating tetrodotoxin-sensitive and tetrodotoxin-resistant voltage-gated sodium channels, but hitherto only little is known about the effects of nerve growth factor on sodium currents in other nociceptor subtypes that express the nerve growth factor receptor TrkA. We previously characterized two reporter mouse lines that allow the unequivocal identification of two important subclasses of TrkA-expressing nociceptors - i.e. neuropeptide Y receptor type 2 (NPY2R+ ) Aδ-fibre nociceptors that mediate pinprick pain and nicotinic acetylcholine receptor alpha-3 subunit (CHRNA3+ ) silent nociceptors, which are the most abundant TrkA+ nociceptors in visceral organs and deep somatic tissues. Here, we utilized these mouse lines to investigate the expression patterns and the possible nerve growth factor-dependent modulation of sodium channels in these neurons using whole-cell patch-clamp recordings and quantitative real-time polymerase chain reaction. We demonstrate that NPY2R+ nociceptors, CHRNA3+ ‘silent’ nociceptors and polymodal C-fibre nociceptors express different combinations of sodium channel α- and β-subunits and accordingly exhibit functionally different sodium currents. Moreover, we demonstrate that nerve growth factor produces robust hyperpolarizing shifts in the half-activation voltage of tetrodotoxin-resistant currents in NPY2R+ nociceptors and polymodal C-fibre nociceptors and also shifts the half-activation of tetrodotoxin-sensitive currents in polymodal C-fibre nociceptors. In silent nociceptors, however, nerve growth factor solely increases the current density of the tetrodotoxin-resistant current but does not alter other sodium channel properties. Considering the different peripheral target tissues and the previously reported roles in different forms of pain of the nociceptor subpopulations that were examined here, our results suggest that nerve growth factor differentially contributes to the development visceral and cutaneous pain hypersensitivity and highlights the importance of developing different therapeutic strategies for different forms of pain.